Learning Strategy Using Picture Methods To Improve Students’ Speaking Ability - Pipit Sevianto (Universitas Cokroaminoto Palopo, 2021)
The objectives in this study are to find out: 1) The image method has an effect on learning English for students in Muhammadiyah Junior High Schools. 2) Speaking ability in learning English in the eyes of Muhammadiyah Senior High School Students 25. 3) How much influence does the drawing method have on speaking skills in learning English in the eyes of Muhammadiyah Senior High School Students 25. This study was designed using a descriptive method with a quantitative approach. The population in this study were 22 Muhammadiyah Junior High School Students, totaling 120 of the 4 classes taken from Class XI. The sample size using the Slovin technique. In the research I did, I used 54 respondents, namely 25 Muhammadiyah high school students. The results of this study are as follows: 1) The picture method for learning English for students at Muhammadiyah Senior High School 25. If you look at the questionnaire for the Picture Method (X) variable, it can be seen from the highest respondent's answer to the answer